The association of plasma asprosin with anthropometric and metabolic parameters in Korean children and adolescents - Kim, Shin-Hee; Kim, Sung Eun; Chun, Yoon Hong (Frontiers in Endocrinology, 2024)
Background: This study aimed to determine the correlation of serum asprosin with anthropometric and metabolic parameters in Korean children and adolescents. Methods: This single-center study included 109 Korean children and adolescents: 62 (56.9%) obese participants with a body mass index (BMI) ≥95th percentile and 47 (43.1%) healthy controls with BMI between the 15th and 85th percentile. Metabolic parameters were measured, including fasting blood glucose, fasting insulin, homeostasis model assessment of insulin resistance (HOMA-IR), triglyceride and glucose (TyG) index, and lipid profiles. Results: Serum asprosin levels were higher in the obese group than in the control group (mean 87.0 vs. 69.3 ng/mL; p = 0.001) and in the IR group than in the non-IR group (mean 98.6 vs. 70.2 ng/mL; p < 0.001). Serum asprosin levels were not associated with sex or pubertal stage. Serum asprosin levels were positively correlated with BMI SDS (r = 0.34; p = 0.002), glycated hemoglobin (HbA1c) (r = 0.25; p = 0.02), glucose (r = 0.33; p = 0.002), insulin (r = 0.44; p < 0.001), HOMA-IR (r = 0.47; p < 0.001), triglyceride (TG) (r = 0.33; p = 0.003), high-density lipoprotein (HDL) cholesterol (r = -0.29; p = 0.008), and TyG index (r = 0.38; p < 0.001). Multiple linear regression analysis indicated that serum asprosin levels were independently associated with HOMA-IR (p < 0.001) and TG/HDL cholesterol ratio (p < 0.001). Conclusions: This study demonstrated an association between serum asprosin levels and obesity and insulin resistance in Korean children and adolescents.